2010
DOI: 10.4067/s0717-95022010000100019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of STZ-Induced Diabetes on the Relative Weights of Kidney, Liver and Pancreas in Albino Rats: A Comparative Study

Abstract: Efectos de la Diabetes Inducida por STZ en los Pesos Relativos de Riñón, Hígado y Páncreas en Ratas Albinas: un Estudio Comparativo * Muhammad Zafar & ** Syed Naeem-ul-Hassan Naqvi ZAFAR, M. & NAEEM-UL-HASSAN NAQVI, S. Effects of STZ-Induced diabetes on the relative weights of kidney, liver and pancreas in albino rats: a comparative study. Int. J. Morphol., 28(1):135-142, 2010. SUMMARY:We studied the effects of streptozotocin (STZ)-induced diabetes on the body weights of animals and the relative weights of kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
96
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 29 publications
(31 reference statements)
29
96
2
3
Order By: Relevance
“…This shows that Garcinia kola has the same function as glibenclamide used in the treatment of diabetes. Just like (17) observed that the diabetic non treated rats looked ill, polydipsia, the relative weights of kidney and liver were increased and the weight of pancreas was unaffected; our diabetic untreated rats showed similar sign of ill looking and polydipsia though their kidney, liver and pancreas were not weighed.…”
Section: Discussionmentioning
confidence: 77%
“…This shows that Garcinia kola has the same function as glibenclamide used in the treatment of diabetes. Just like (17) observed that the diabetic non treated rats looked ill, polydipsia, the relative weights of kidney and liver were increased and the weight of pancreas was unaffected; our diabetic untreated rats showed similar sign of ill looking and polydipsia though their kidney, liver and pancreas were not weighed.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the evaluation of histopathological studies demonstrated that activate AMPK signaling pathway attenuate the kidney tissue damage that is caused by STZ-diabetes. STZ-induced type 1 diabetic rats are associated with severe decrease of body weight caused by hyperglycemia, loss of tissue proteins (14), muscular tissue and adipose tissue (15). Additionally, the increase in the levels of serum uric acid and creatinine (16) and the decrease in the levels of serum albumin and total protein (17) have been associated with diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zafar and Naqvi [42] and Saumya and Basha [43], reported that STZ decompose inside the cell to form carbonium ions that alkylate DNA and decrease cellular nicotinamide adenine nucleotide (NAD) level which may adversely affect beta cells by interrupting respiratory enzyme activity and alteration of their mitochondrial function leading to irreversible cellular necrosis and death of beta cells resulting in permanent hyperglucemia, this changes lead to suppression and disturbance of biosynthesis and insulin secretion. Moreover, Cemek et al [44] also found that hyperglycemia is due to irreversible destruction of beta islet cells of the pancreas by STZ, causing a reduction of insulin secretion (hypoinsulinemia).…”
Section: Discussionmentioning
confidence: 99%